Hominin locomotion and evolution in the Late Miocene to Late Pliocene. Issue 178 (May 2023) - Stamos, Peter A.; Alemseged, Zeresenay
Abstract: In this review, we present on the evolution of the locomotor adaptation of hominins in the Late Miocene to Late Pliocene, with emphasis on some of the prominent advances and debates that have occurred over the past fifty years. We start with the challenging issue of defining hominin locomotor grades that are currently used liberally and offer our own working definitions of facultative, habitual, and obligate bipedalism. We then discuss the nature of the Pan - Homo last common ancestor and characterize the locomotor adaptation of Sahelanthropus, Orrorin, and Ardipithecus— often referred to as facultative bipeds—and examine the debates on the extent of bipedality and arboreality in these taxa. Moreover, the question of Middle Pliocene hominin locomotor diversity is addressed based on information derived from the 'Little Foot' specimen from Sterkfontein, footprints from Laetoli, and the Burtele Foot in Ethiopia. Our review suggests that the most convincing evidence for locomotor diversity comes from Burtele, whereas the evidence from Sterkfontein and Laetoli is unconvincing and equivocal, respectively. Finally, we address the decades old issue of the significance of arboreality in the otherwise habitual biped, Australopithecus, with emphasis on Australopithecus afarensis and its implications for the paleobiology of these creatures. We conclude that many of the apelike features encountered, mostly in the upper part of the Australopithecus skeleton, were retained for their significance in climbing. Approaches that have investigated character plasticity and those exploring internal bone structure have shown that the shoulder and limbs in Au. afarensis and Australopithecus africanus were involved in arboreal activities that are thought to be key for feeding, nesting, and predator avoidance. We conclude that many of the so-called retained ape-like features persisted due to stabilizing selection, that early hominins engaged in a considerable amount of arboreality even after Australopithecus had become a habitual biped, and arboreality only ceased to be an important component of hominin locomotor behavior after the emergence of Homo erectus .